2023
DOI: 10.1038/s41467-023-39890-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural delineation and computational design of SARS-CoV-2-neutralizing antibodies against Omicron subvariants

Abstract: SARS-CoV-2 Omicron subvariants have evolved to evade receptor-binding site (RBS) antibodies that exist in diverse individuals as public antibody clones. We rationally selected RBS antibodies resilient to mutations in emerging Omicron subvariants. Y489 was identified as a site of virus vulnerability and a common footprint of broadly neutralizing antibodies against the subvariants. Multiple Y489-binding antibodies were encoded by public clonotypes and additionally recognized F486, potentially accounting for the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…This novel lineage carries numerous mutations known to allow mAb evasion (Wang et al ., 2023a), including the K356T substitution conferring resistance to Sotrovimab (Addetia et al ., 2023) (Ragonnet-Cronin et al ., 2023). Novel mAbs are under pre-clinical and clinical development (Cao et al ., 2022a; Moriyama et al, 2023; Park et al, 2022a). It will be worth carefully scrutinizing their antiviral activity against BA.2.86 and other emerging subvariants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This novel lineage carries numerous mutations known to allow mAb evasion (Wang et al ., 2023a), including the K356T substitution conferring resistance to Sotrovimab (Addetia et al ., 2023) (Ragonnet-Cronin et al ., 2023). Novel mAbs are under pre-clinical and clinical development (Cao et al ., 2022a; Moriyama et al, 2023; Park et al, 2022a). It will be worth carefully scrutinizing their antiviral activity against BA.2.86 and other emerging subvariants.…”
Section: Discussionmentioning
confidence: 99%
“…This novel lineage carries numerous mutations known to allow mAb evasion 28 , including the K356T substitution conferring resistance to Sotrovimab 51 52 . Novel mAbs are under pre-clinical and clinical development 11,60,61 . It will be worth scrutinizing their antiviral activity against BA.2.86.1/JN.1 and other emerging subvariants.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the clinical application of anti-RBD antibodies has led to reduced neutralization and inhibitory activities. 22 , 26 , 30 , 31 , 58 Although efforts to develop broadly neutralizing antibodies that target pan-coronavirus conserved epitopes are actively underway, 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 the possibility of emerging immune-evading mutant variants remains, posing a recurrent challenge to monoclonal antibody therapy. Therefore, the exploration of alternative approaches is attractive.…”
Section: Discussionmentioning
confidence: 99%
“…Moriyama et al reported the design of antibody NIV-10/FD03 using computational techniques, leveraging the Y489 residue in the receptor-binding site of SARS-CoV-2 RBD. 114 This antibody effectively binds to Omicron XBB variants, even in the presence of mutations at position 486, and successfully neutralizes XBB.1.5. This achievement provided a foundation for developing therapeutics that can resist viral escape.…”
Section: ■ Cpd Strategies Targeting Escape Mutants To Curtail New Var...mentioning
confidence: 99%
“…These methodologies empower researchers to foresee and tackle the hurdles posed by viral variants, providing them with the flexibility to adjust their strategies as required. Moriyama et al reported the design of antibody NIV-10/FD03 using computational techniques, leveraging the Y489 residue in the receptor-binding site of SARS-CoV-2 RBD . This antibody effectively binds to Omicron XBB variants, even in the presence of mutations at position 486, and successfully neutralizes XBB.1.5.…”
Section: Cpd Strategies Targeting Escape Mutants To Curtail New Variantsmentioning
confidence: 99%